Dyspepsia in Clinical Practice - Duvnjak, Marko; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Although dyspepsia has been investigated for a long period of time, there is no international agreement on what constitutes this condition nor any standardized guidelines. National guidelines followed by practitioners in different countries vary in diagnostic and therapeutic approach, underlining the necessity for a unique definition worldwide. Dyspepsia in Clinical Practice summarizes the current guidelines while offering a unified, practical definition of dyspepsia, and a diagnostic algorithm with an emphasis on the upper gastrointestinal endoscopy and rational first-line therapeutic approach based on epidemiology, pathophysiology, clinical presentation, diagnostic workup and response to previous therapy. Up-to-date scientific information about dyspepsia is presented from a practical, clinician's point of view, brought by experts in their field. The volume addresses Dyspepsia in childhood and in the elderly, a very important issue often insufficiently emphasized in the literature. Guidelines are provided that can be easily followed in clinical practice, leading to a reduction in costs and patient safety. Dyspepsia in Clinical Practice will be of great value to gastroenterologists, internists, primary care physicians, pediatricians, infectious disease specialists, residents and fellows in training. Dyspepsia in Clinical Practice.
Introduction -- The Definition of Dyspepsia -- Subgroups of Dyspepsia -- Epidemiology -- Structural Causes of Dyspepsia -- Functional (Nonulcer) Dyspepsia.- How to Diagnose Dyspepsia.– Differential Diagnosis – Overlap with Gastroesophageal Reflux Disease and Irritable Bowel Syndrome -- Management of Uninvestigated Dyspepsia -- Management of Helicobacter Pylori Infection -- Management of Peptic Ulcer Disease -- Therapeutic Approach in Functional (Nonulcer) Dyspepsia -- Prognosis -- Quality-of-Life Issues -- Economic Analyes of Present Management Strategies and Nonprescription Therapy in Treatment of Dyspepsia.-Dyspepsia in Children: Epidemiology, Clinical Presentation and Causes -- Diagnostic Tests and Treatment of Dyspepsia in Children -- Dyspepsia in the Elderly -- Diabetes Mellitus and Dyspepsia.
Keywords: Gastroenterology .; Primary care (Medicine).; Infectious diseases; Pediatrics; Gastroenterology; Primary Care Medicine; Infectious Diseases; Pediatrics